Perbedaan Tingkat Kecemasan pada Ibu Pre Seksio Caesarea di RSIA Kasih Ibu dan RSUP. Prof. Dr. R. D. Kandou Manado - Pawatte, Inggriet; Pali, Cicilia; Opod, Henri (UNIVERSITAS SAM RATULANGI, 2013)
Anxiety is signal that disenchant themselves to take action overcome the threats. The action sectio caesarean with various complication evoked anxiety. Excessive anxiety can result inhibition seem that the process of labor operating. Availability hospital services that profesional and qualified important to ensure process labor operating rnning smoothly so as to reduce feelings anxiety. Purpose research is find out the different levels anxiety mother pre sectio caesarean in RSIA Kasih Ibu dan RSUP. Prof. Dr. R. D. Kandou Manado. The research usin the analytic method apply plan crossectional. Sampling using consecutive sampling. Taking data done on 12 October-12 December 2012. Instrument used is HARS to measure level anxiety the mothers pre sectio caesarean and questionnare of service quality to service quality in each hospital. The result showed that there are difference mothers pre section caesarean in both hospitals. Based on the results the study suggested that the public better understand the emotional state the mother who will face action caesarean Caesarea, and to provide emotional support to the mother's contribution. For hospitals, to further improve its service quality as expected by patients. Keywords: Level anxiety, Sectio Caesarean, Hospital